Aromatic disulfide epoxy vitrimer packaged electronic devices: Nondestructive healing and recycling. (22nd August 2022) - Zhang, Huan; Zhou, Lin; Zhang, Fengtian; Yang, Qing; Chen, Maobin; Chen, Zhongtao; Zhang, Yinyu; Xiao, Peishuang; Yu, Shujun; Song, Lixian; Wu, Yeping; Zhao, Xiuli; et al.
Abstract: Electrical and electronic equipment (EEE) that greatly enhances global living standards has become indispensable in modern societies. In EEE, most electronic devices are protected by epoxy electronic packaging that exhibits outstanding mechanical property, high electrical resistivity and excellent solvent resistance. However, due to thermolability of electronic components and insolubility of epoxy, it is impossible to heal and recycle the packaged electronic devices non-destructively, resulting in a huge amount of e-waste during manufacturing and consumption. Herein, aromatic disulfide epoxy vitrimer packaged electronic devices were proposed, in which nondestructive healing and recycling were achieved. The epoxy vitrimer was prepared from aromatic disulfide-based epoxy and aliphatic amines at moderate temperature (≤100 °C), resulting in highly cross-linked networks, excellent solvent resistance and good thermal stability. The tensile strength was ∼71.9 MPa and the glass transition temperature was ∼115 °C. Moreover, it exhibited comparable electrical resistivity to reference epoxy, while lower dielectric constant was observed. In epoxy vitrimer packaged LED light, cracks could be readily healed at 150 °C through aromatic disulfide metathesis in networks, while the epoxy vitrimer exhibited topology freezing transition at ∼118 °C. Besides, relying on reactions between aromatic disulfide bonds and outer thiol groups, the epoxy vitrimer packaged LED light, printed circuit board and integrated circuit could be non-destructively recycled, while the epoxy vitrimer was degradable on demand. The aromatic disulfide epoxy vitrimer packaged electronic devices with nondestructive healing and recycling properties provide a better way to deal with substandard electric products and retired ones, leading to e-waste reducing, resource recycling and environment-friendly development in EEE. Graphical abstract: Image 1 Highlights: An aromatic disulfide epoxy vitrimer that reacted at moderate temperature was prepared to package electronic devices. The epoxy vitrimer packaged electronic devices exhibited nondestructive crack-healing properties. The epoxy vitrimer packaged LED light, printed circuit board and integrated circuit were non-destructively recycled.